McDonald's Corporation : who is responsible for America's obesity? - Wysocki, Julia; Dennhardt, Allison; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
McDonalds Corporation, the leader among U.S. franchise quick-service restaurants, found in 2002 that its reputation for steady growth and strong profitability were slipping. At the same time, much of the market for fast food in North America began migrating to lower-calorie, healthier alternatives. Fast food and social trend critics began blaming quick service restaurants for a wide range of health problems, including obesity and weight-related illnesses. New York attorney Samuel Hirsch filed a class action suit on behalf of obese and overweight children against McDonalds, alleging that the fast-food chain "negligently, recklessly and/or intentionally" marketed food products that are "high in fat, salt, sugar, and cholesterol" while failing to warn of those ingredients links to "obesity, diabetes, coronary heart disease, high blood pressure, strokes, elevated cholesterol intake, related cancers," and other conditions. McDonalds reputation, profitability, and future are at stake as it prepares in 2003 to defend itself, its products, and its business.
Originally published: Wysocki, J., Dennhardt, A., & ORourke, J. S. (2003). McDonalds Corporation: Who is responsible for Americas obesity? 06-06. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; McDonald's Corporation; Fast food restaurants -- Health aspects; Fast food restaurants -- Marketing; Children -- Nutrition; Social responsibility of business